Solve for y fifth root of y-3+5=0

Math
y-35+5=0
Subtract 5 from both sides of the equation.
y-35=-5
To remove the radical on the left side of the equation, raise both sides of the equation to the power of 5.
y-355=(-5)5
Simplify each side of the equation.
Tap for more steps…
Multiply the exponents in ((y-3)15)5.
Tap for more steps…
Apply the power rule and multiply exponents, (am)n=amn.
(y-3)15⋅5=(-5)5
Cancel the common factor of 5.
Tap for more steps…
Cancel the common factor.
(y-3)15⋅5=(-5)5
Rewrite the expression.
(y-3)1=(-5)5
(y-3)1=(-5)5
(y-3)1=(-5)5
Simplify.
y-3=(-5)5
Raise -5 to the power of 5.
y-3=-3125
y-3=-3125
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 3 to both sides of the equation.
y=-3125+3
Add -3125 and 3.
y=-3122
y=-3122
Solve for y fifth root of y-3+5=0

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top